Applying species distribution modelling to a data poor, pelagic fish complex: the ocean sunfishes. (19th June 2017) - Phillips, Natasha D.; Reid, Neil; Thys, Tierney; Harrod, Chris; Payne, Nicholas L.; Morgan, Cheryl A.; White, Hannah J.; Porter, Siobhán; Houghton, Jonathan D.R.
Abstract: Aim: Conservation management of vulnerable species requires detailed knowledge of their spatial and temporal distribution patterns. Within this context, species distribution modelling (SDM) can provide insights into the spatial ecology of rarely encountered species and is used here to explore the distribution pattern of ocean sunfishes ( Mola mola and M. ramsayi ). Both species are prone to high levels of bycatch and are classified respectively as Globally Vulnerable and Not Assessed by the IUCN; although their overall range and drivers of distribution remain poorly defined. Here, we constructed suitable habitat models for Mola spp. on a global scale and considered how these change seasonally to provide a much needed baseline for future management. Location: Global. Methods: Sighting records collected between 2000 and 2015 were used to build SDMs and provided the first global overview of sunfish seasonal distribution. Post hoc analyses provided a quantitative assessment of seasonal changes in total range extent and latitudinal shifts in suitable habitat. Results: Mola is a widely distributed genus; however, sightings exhibited significant spatial clustering most notably in coastal regions. SDMs suggested that Mola presence was strongly dependent on sea surface temperatures with highest probability of presence between 16 and 23°C. The models identified significant variation in seasonal range extent with latitudinal shifts throughout the year; although large areas of suitable year‐round habitat exist globally. Main conclusions: We provided the first assessment of Mola distribution on a global scale, with evidence of a wide latitudinal range and significant clustering in localized "hotspots" (notably between 40–50°N). By assessing the results of SDMs alongside evidence from published satellite tagging studies, we suggest that the species within the genus Mola are highly mobile, acting as facultative seasonal migrants. By identifying key suitable habitat alongside potential movement paths, this study provides a baseline that can be used in active conservation management of the genus.